SYSTEMIC FUNCTIONAL LINGUISTICS IN EFL CLASSROOM: ANALYZING STUDENTS’ RECOUNT TEXT THROUGH THREE METAFUNCTIONS - Soni, Mohammad; Nugraha, Irsyad; Umami, Riza; Andini, Anggi Setia (UIN Alauddin Makassar, 2025)
One of the main challenges in learning English as a Foreign Language (EFL) at the Junior High School level is students' low ability to write recount texts that conform to the correct grammatical rules and text structure. Although recount texts are a type of text that is routinely taught, many students still experience difficulties in terms of the use of proper grammar, development of ideas, and cohesion between parts of the text. This suggests the need for an in-depth evaluation of the quality of students' texts, not only in terms of content but also in terms of their structure and function in the context of communication. This study is significant because it provides a thorough analysis of students' recount texts using the Systemic Functional Linguistics (SFL) approach through three metafunctions: interpersonal, experiential, and textual. Thus, this study not only reveals the extent to which students fulfill the expected generic structures and linguistic features but also identifies areas of weakness, particularly in aspects such as tense usage, subject-verb congruence, and cohesion devices. This finding is crucial for informing the development of more targeted learning strategies, particularly in enhancing the grammatical consistency and cohesion of students' texts. By understanding the linguistic aspects that students have not mastered, teachers can design more targeted teaching interventions to improve the overall quality of student writing.